2000
DOI: 10.1016/s0092-8674(00)80626-1
|View full text |Cite
|
Sign up to set email alerts
|

Drosophila p53 Is a Structural and Functional Homolog of the Tumor Suppressor p53

Abstract: The importance of p53 in carcinogenesis stems from its central role in inducing cell cycle arrest or apoptosis in response to cellular stresses. We have identified a Drosophila homolog of p53 ("Dmp53"). Like mammalian p53, Dmp53 binds specifically to human p53 binding sites, and overexpression of Dmp53 induces apoptosis. Importantly, inhibition of Dmp53 function renders cells resistant to X ray-induced apoptosis, suggesting that Dmp53 is required for the apoptotic response to DNA damage. Unlike mammalian p53, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
351
1
12

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 374 publications
(377 citation statements)
references
References 83 publications
(1 reference statement)
13
351
1
12
Order By: Relevance
“…[41][42][43] Furthermore, ectopic apoptosis induced by p53 overexpression was not affected by LKB1 dosage reduction (Supplementary Figure 2e). Therefore, taken together with previous data showing that p53 is dispensable for LKB1-dependent apoptosis (Figure 4c-e), we concluded that LKB1 is dispensable for the p53-dependent cell death in Drosophila.…”
Section: Lkb1 Is Dispensable For P53-dependent Apoptosismentioning
confidence: 93%
See 1 more Smart Citation
“…[41][42][43] Furthermore, ectopic apoptosis induced by p53 overexpression was not affected by LKB1 dosage reduction (Supplementary Figure 2e). Therefore, taken together with previous data showing that p53 is dispensable for LKB1-dependent apoptosis (Figure 4c-e), we concluded that LKB1 is dispensable for the p53-dependent cell death in Drosophila.…”
Section: Lkb1 Is Dispensable For P53-dependent Apoptosismentioning
confidence: 93%
“…19,[41][42][43] Therefore, we questioned whether LKB1-dependent apoptosis requires p53 activity. When a dominant-negative p53 was expressed by the gmrGal4 driver, the ionizing radiation-dependent apoptosiswhich is fully dependent on p53 -was specifically suppressed in the gmr-expressing region (Figure 4c, d), demonstrating that the dominant-negative p53 is sufficient to inhibit endogenous p53 activity.…”
Section: Lkb1-induced Apoptosis Is Caspase Dependent But P53 Independentmentioning
confidence: 99%
“…However, only one transcript has been described for drosophila p53 gene (dp53). 56,57 By amplifying capped transcripts, we identified two additional transcripts containing two novel exons (A and B) located upstream of the previously identified dp53 gene. 15 One mRNA encodes for a drosophila p53 protein of 495 aa (110 aa longer than the dp53 initially published) with a longer N-terminal domain containing the conserved transactivation domain FxxcW.…”
Section: Conservation Through Evolution Of the P53 Gene Structurementioning
confidence: 99%
“…The in vivo apoptotic activity of dmp53 was initially shown by ectopic overexpression in the eye, which induced apoptosis. 3,5 These findings were further supported by genetic lossof-function studies, which established that dmp53 is required for transcriptional induction of rpr proteins (rpr, hid, skl) and for radiation-induced apoptosis. 3 General development was not affected in the dmp53 mutants, [19][20][21] but mild defects in longevity and fertility were found.…”
Section: Drosophila Melanogastermentioning
confidence: 81%
“…[3][4][5] More recently, a longer 495 amino acid isoform and a shorter 110 amino acid isoform were also reported. 9 The anatomic structure of dmp53 is similar to mammalian p53.…”
Section: Drosophila Melanogastermentioning
confidence: 95%